Observation of Oral Contrast Media Filling Into Lumen Appendix - Faradilla litiloly1, Hartono Yudi Sarastika1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: CT scan has become the imaging modality of choice in diagnosing appendicitis in unusual cases, replacing appendicogram with very little reliability. However, there is still an appendicogram demand in particular hospital in Indonesia. Objectives: This study aimed to obtain information on lumen appendix filling pattern with multi slice Multislice computed tomography (MSCT) scan using oral contrast media in patients without clinical appendicitis. Thus, it is able to provide additional information in the appendicogram interpretation. Method: This study was descriptive observational to 30 subjects selected by consecutive from April to June 2012. Subjects who underwent an abdominal MSCT scan using oral contrast media were analyzed descriptively by sex, age and lumen appendix filling pattern. Results: 30% of patients were men and women by 70%. The most common age group is 51-60 years (50%). Appendix of non-filling of 56.6%, partial filling of 43.3%, and no full filling appendix was obtained. Conclusion: Appendix filling as an indicator of the presence of appendicitis was not reliable in an abdominal MSCT scan using oral water soluble contrast, thus it needs to be considered when interpreting the appendicogram results